Research impact assessment of a Canadian digital health funding program: a case study - Jessica Nadigel; Bahar Kasaai; Halla Thorsteinsdóttir; Susan Rogers; Meghan McMahon; R. Jane Rylett; Richard H. Glazier (Health Research Policy and Systems, 2025)
Abstract Background Digital innovations have the potential to enhance equitable access to health systems, improve care integration and support learning health systems. Research funders make substantial investments in digital health research to advance the uptake of evidence-informed digital solutions within health systems, yet their impacts on health and health system outcomes, health equity, policy and practice remain poorly understood. Research impact assessments (RIAs) serve as a vital tool for funders to examine the links between research investments and real-world change. The Canadian Institutes of Health Research commissioned an RIA on its largest digital health program, the eHealth Innovations Partnership Program (eHIPP), to understand the program’s outputs and impacts. Methods This study applied two complementary frameworks, the Canadian Academy of Heath Science’s (CAHS) Making an Impact Framework and the Canadian Health Services and Policy Research Alliance’s (CHSPRA) Informing Decision-Making Framework, to assess the research impact of the eHIPP program, funded from 2015 to 2021. A mixed-methods approach was taken to collect and analyse data from eHIPP grant recipients and their partners. Results The eHIPP program supported 22 research teams through a total investment of CAD$ 42M. The RIA revealed impacts in the areas of capacity development, knowledge creation, informing decision-making and health outcomes. The teams generated 36 co-designed, evidenced-informed solutions, 79 publications, 194 presentations and 38 media interviews or articles. Solutions were reported to influence health system practice (52%) and policy (33%), improve health outcomes (62%), enhance equitable access to care (62%), improve patient (62%) and provider experience (52%), increase cost-effectiveness (52%), enhance population health (48%) and improve health equity (43%). Conclusions This RIA study highlights the importance of stakeholder collaboration, robust partnerships and co-design approaches in effectively integrating patient-centred digital health solutions into health systems. These elements are key to advancing the Quintuple Aim (improved cost, population health and equity and experience of patients and providers) and supporting evidence-informed decisions. This paper presents a first case study applying the CAHS and CHSPRA frameworks to assess the impacts of a large digital health funding program. Further, it explores the program’s outcomes and impacts and highlights considerations, successes and challenges for funders when applying RIA.